Causal Dynamics of Paranoid Personality Disorder - Husna, Mai Tiza (ANFUSINA: Journal of Psychology, 2024)
Personality disorder is one of the chronic psychological problems because it affects many aspects of individuals. Individuals with personality disorders are usually unaware that they are suffering from psychological problems. Paranoid personality disorder is a specific type of personality disorder. The characteristic of this disorder is an overbearing suspicion of others. The exact cause of this personality disorder is unknown because there have been few studies on it. The purpose of this study is to discover and describe the causes of the subject's paranoid personality disorder. This study is qualitative and has a case study design. The subject of this study is a 29-year-old man with paranoid personality disorder. The data collection techniques employed were interviews, observations, psychological assessments, and documentation. Thematic analysis was used to examine the data. The findings revealed that traumatic events in childhood were the primary cause of the subject's personality disorder. The events involved parental violence and being a victim of bullying. The subject struggled to adjust and form social relationships with others as a result of his early life experiences. He had difficulty making friends and was bullied throughout his school years. These painful experiences with others convinced him that interacting with others was dangerous, so he continued to suspect everything the people around him did. The finding demonstrates how traumatic events from the past can cause paranoid personality disorder.